Scientific and practical recommendations for the sustainable development goals implementation using standards ISO - Zamkovyj , Rostislav (Theory and Practice of Public Administration, 2019)
The article proposes scientific and practical recommendations for the sustainable development goals implementation using ISO standards, defined by a specific indicator system for structured and consistent support for sustainable, intelligent and adaptive community management. In particular, all goals and tasks related to the sustainable management system implementation are oriented towards the United Nations goals in the field of sustainable development and their potential for implementation in communities; all strategies, programs, projects, plans and services need to be directed towards goal-based goals. All tasks can be estimated by the values ​​of the indicators and metrics contained in the standards of ISO 37101:2016; ISO 37120:2014 and ISO/TS 37151:2015. Also, the use of these standards enables: to create a specific community structure (community) that has the authority to manage sustainable development; with a focus on engaging all stakeholders to identify and implement a sustainable development strategy that reflects the needs of the community; use the principles and methodologies included in the standard that reflect the best international practice of sustainable development and are compatible with the development in this sector; to identify the importance of jointly solving the goals, strategies and timing for achieving them - this provides a wider visualization of a wide range of stakeholders regarding the community approach to sustainable development. At the same time, if communities need to consider additional or alternative tasks, iterative cross-reference analysis of goals and objectives is necessary to determine their relevancy and timeliness. The article provides examples of tasks for the sustainable development in communities goals realization, in particular, a number of issues that help to determine what is relevant to the case and are suitable for solving the tasks, which makes it possible to assess the significance of the task and the level of the community influence in translating this task from most important in the least important.